2018
DOI: 10.1002/bit.26839
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput identification of factors promoting neuronal differentiation of human neural progenitor cells in microscale 3D cell culture

Abstract: Identification of conditions for guided and specific differentiation of human stem cell and progenitor cells is important for continued development and engineering of in vitro cell culture systems for use in regenerative medicine, drug discovery, and human toxicology. Three-dimensional (3D) and organotypic cell culture models have been used increasingly for in vitro cell culture because they may better model endogenous tissue environments. However, detailed studies of stem cell differentiation within 3D cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Amongs others, CHIR is a small molecule used to promote neuroprogenitor homeostasis and neural induction. with CHIR significantly enhanced neurogenesis, while simultaneously decreasing astrocyte differentiation (Nierode et al, 2019).…”
Section: Gsk-3 β-Antagonismmentioning
confidence: 88%
See 1 more Smart Citation
“…Amongs others, CHIR is a small molecule used to promote neuroprogenitor homeostasis and neural induction. with CHIR significantly enhanced neurogenesis, while simultaneously decreasing astrocyte differentiation (Nierode et al, 2019).…”
Section: Gsk-3 β-Antagonismmentioning
confidence: 88%
“…CHIR was shown to restore WβC‐signalling and to rescue DAergic differentiation in iPSC‐derived NSCs from Gaucher's disease patients, exhibiting developmental defects due to downregulation of canonical WβC‐signalling (Awad et al, ). Recently, Nierode et al () reported high‐throughput identification of factors promoting neuronal differentiation of human neural progenitor cells in microscale 3D cell cultures. In this study, the authors looked at a microarray chip‐based platform to screen the individual and combined effects of 12 soluble factors on the neuronal differentiation of a human neural progenitor cell line (ReNcell VM) encapsulated in microscale 3D Matrigel cultures, revealing that the combined treatment of trans ‐retinoic acid with CHIR significantly enhanced neurogenesis, while simultaneously decreasing astrocyte differentiation (Nierode et al, ).…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 99%
“…6 and Additional file 1: Figure S6). We also measured the brain-derived neurotrophic factor (BDNF) and the nerve growth factor-β (NGF-β) because they provide signaling and trophic support during NPC differentiation [48]. The levels of these growth factors were not detectable in NPC culture media 3 days after differentiation.…”
Section: Rage Inhibition Selectively Affects Differentiation Of Npcs mentioning
confidence: 99%
“…Furthermore, coupling microfluidic systems with 3D culture can improve differentiation and enhance neural migration. Recently a microarray chip-based platform was used to grow 3D cultures of neural progenitor cells and assess the effects of soluble factors on neuronal differentiation (Nierode et al, 2018).…”
Section: Technical Limitations and Potential Future Advancesmentioning
confidence: 99%